Retrospective study on the efficacy of a low-carbohydrate diet for impaired glucose tolerance - Maekawa S (Dove Medical Press, 2014)
Satoshi Maekawa,1 Tetsuya Kawahara,2 Ryosuke Nomura,1 Takayuki Murase,1 Yasuyoshi Ann,1 Masayuki Oeholm,1 Masaru Harada31Department of Gastroenterology and Hepatology, 2Division of Endocrinology and Metabolism, Department of Internal Medicine, Japan Labor Health and Welfare Organization, Niigata Rosai Hospital, Joetsu, Niigata, Japan; 3Third Department of Internal Medicine, University of Occupational and Environmental Health, Iseigaoka, Yahata-nishi-ku, Kitakyushu, Fukuoka, JapanBackground: In recent years, the number of people with impaired glucose tolerance (IGT) has increased steadily worldwide. It is clear that the prevention of diabetes is important from the perspective of public health, medical care, and economics. It was recently reported that a low-carbohydrate diet (LCD) is useful for achieving weight loss and glycemic control, but there is no information about the effects of the LCD on IGT. We designed a 7-day in-hospital educational program focused on the LCD for IGT.Methods: The subjects were 72 patients with IGT (36 in the LCD group and 36 in the control group) who were enrolled from April 2007–March 2012 and followed for 12 months. We retrospectively compared the LCD group with the control group.Results: In 69.4% of the LCD group, blood glucose was normalized at 12 months and the 2-hour plasma glucose level in the oral glucose tolerance test (OGTT) was reduced by 33 mg/dL. In addition, the incidence of diabetes was significantly lower in the LCD group than in the control group at 12 months (0% versus 13.9%, P=0.02). The LCD group showed a significant decrease in fasting plasma glucose, hemoglobin A1c, the homeostasis model of assessment of insulin resistance value, body weight and serum triglycerides (TGs) at 12 months, while there was a significant increase of the serum high-density lipoprotein (HDL) cholesterol level.Conclusion: The LCD is effective for normalizing blood glucose and preventing progression to type 2 diabetes in patients with IGT.Keywords: type 2 diabetes, low-carbohydrate diet, impaired glucose tolerance